2019
DOI: 10.4491/eer.2019.373
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbon and nitrogen on bioclogging in a sand grain managed aquifer recharge (MAR)

Abstract: Managed aquifer recharge (MAR), an intentional storage of excess water to an aquifer, is becoming a promising water resource management tool to cope with the worldwide water shortage. Bioclogging is a commonly encountered operational issue that lowers hydraulic conductivity and overall performance in MAR. The current study investigates the impact of carbon and nitrogen in recharge water on bioclogging in MAR. For this investigation, continuous-flow columns packed with sand grains were operated with influents h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…During reinjection, clogging of the aquifer can be categorized as physical, chemical, and bio-clogging [4]. It can result from natural physicochemical processes caused by filtration of suspended solids in reinjection water or biological reactions in porous soil media caused by the accumulation of bacterial cells and the production of extracellular polysaccharides [5] [6]. Among them, bio-clogging often leads to a reduction in the hydraulic conductivity of aqueous media by several orders of magnitude [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…During reinjection, clogging of the aquifer can be categorized as physical, chemical, and bio-clogging [4]. It can result from natural physicochemical processes caused by filtration of suspended solids in reinjection water or biological reactions in porous soil media caused by the accumulation of bacterial cells and the production of extracellular polysaccharides [5] [6]. Among them, bio-clogging often leads to a reduction in the hydraulic conductivity of aqueous media by several orders of magnitude [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Constructed wetlands (CWs) have been successfully employed to treat domestic sewage for its easy operation and maintain [11,12]. Consequently, the application of CWs for the purification of wastewater has been recently proposed as an alternative for the wastewater treatment and reuse [13][14][15].…”
Section: Introductionmentioning
confidence: 99%